The Effectiveness of Problem Based Learning Model on Critical Thinking Skills on the Topic of Appreciating the Environment and Local Culture - Az Zahra Salsa Billa; Eko Priyanto; Ratna Kartikawati (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the effectiveness of the Problem-Based Learning (PBL) model on critical thinking skills on Appreciating the Environment and Local Culture at SMP Negeri 8 Purwokerto. The method used in this study is quasi-experimental with a quantitative approach. The population in this study consists of Grade VII students at SMP Negeri 8 Purwokerto. The sample size is 70 students, selected through purposive sampling, with class VII D as the experimental group (n=35) and class VII A as the control group (n=35). Data collection techniques include unstructured interviews, observation, documentation, and questionnaires. The research findings indicate a significant effect of the Problem-Based Learning model on students' critical thinking skills, with a significance value of 0.769. This means that the independent variable (X), the Problem-Based Learning model, has a significant effect of 76.9% on the dependent variable (Y), which is critical thinking skills. The results demonstrate that implementing the Problem-Based Learning model significantly enhances critical thinking skills among Grade VII students at SMP Negeri 8 Purwokerto.